Mechanical acne - a review of contributing factors and diagnostic-therapeutic approach - Anna Gorajek; Małgorzata Kudan; Aleksandra Osiejewska; Anna Grądzik; Karolina Mikut; Dominika Wojtachnio; Izabela Nowakowska; Jakub Bartoszewicz (Kazimierz Wielki University, 2022)
Introduction and purpose: Acne is a diverse, multifactorial disease. A specific subtype of acne is mechanical acne, which is recurrent acne that occurs at the site of physical trauma to the skin due to repeated mechanical or frictional obstruction of the pilosebaceous outlet. The aim of the article is to present the available information on the pathophysiology, clinical picture, diagnosis, and treatment of mechanical acne. Description of the state of knowledge: Mechanical acne may be a complication of preexisting acne or can occur independently in a patient with no previous history of acne. Inflammatory acneiform papules and pustules result from friction from repetitive rubbing, stretching, squeezing, pressure, tension, pinching, or pulling of the skin accompanied by heat, pressure, moisture, and occlusion. Mechanical stress on the skin can be triggered by any pressure or friction inducing physical factors, such as tight clothing, sports gear, accessories, medical equipment, seat backs or hands. Mechanical acne most commonly occurs in athletes and develops from wearing tight-fitting clothing, accessories, or equipment. The severity of lesions increases with excessive sweating and overheating of the skin. In the era of the COVID-19 pandemic, the incidence of mechanical acne caused by prolonged wearing of protective masks ("maskne") has also increased. Summary: The most important aspect of mechanical acne treatment and preventions is the identification and elimination (or at least minimization) of the inciting factors. Supporting activities include maintaining cleanliness, proper skin care and applying topical acne treatments. Some patients require oral pharmacotherapy. Preventing recurrence of mechanical acne is important as it can leave unsightly scars and skin discoloration.